Towards an East German wage curve: NUTS boundaries, labour market regions and unemployment spillovers - Reinhold Kosfeld; Christian Dreger (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
The relevance of spatial effects in the wage curve can be rationalized by the model of monopsonistic competition in regional labour markets. However, distortions in extracting the regional unemployment effects arise in standard regional (i.e. NUTS) classifications as they fail to adequately capture spatial processes. In addition, the nonstationarity of wages and unemployment is often ignored. Both issues are particularly important in high unemployment regimes like East Germany where a wage curve is difficult to establish. In this paper, labour market regions defined by economic criteria are used to examine the existence of an East German wage curve. Due to the nonstationarity of spatial data, a global panel cointegration approach is adopted. By specifying a spatial error correction model (SpECM), equilibrium adjustments are investigated in time and space. The analysis gives evidence on a locally but not a spatially cointegrated wage curve for East Germany.
Keywords: J30; J60; C33; R15; 330; wage curve; labour market regions; global cointegration; spatial error-correction model